The Effect of Discounts, Cashback and Promotions on Impulse Buying through Hedonic Shopping Motivation as an Intervening Variable in Shopee Consumers Islamic Perspective: A Case Study of Students in Banyuwangi Regency - Joharul Fathoni (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
The development of communication technology in the era of globalization makes it easier for people to access information, including in online shopping activities through e-commerce platforms. Shopee is one of the most popular e-commerce in Indonesia that offers a variety of products, ranging from fashion to daily needs. This study aims to analyze the influence of discounts and promotions on hedonic shopping motivation and impulse buying, as well as the effect of hedonic shopping motivation on impulse buying in an Islamic perspective on Shopee application users among Banyuwangi students. This research is included in the type of explanatory research, which aims to explain the causal relationship between variables through hypothesis testing. The analysis method used was multiple linear regression with the model: Y = a₀ + b₁X₁ + b₂X₂ + b₃X₃ + b₄X₄ + e. The results of the study show that discounts do not have a significant effect on hedonic shopping motivation, but promotions have a significant influence. Meanwhile, discounts and promotions have a significant effect on impulse buying, while cashback has no significant effect. In addition, hedonic shopping motivation has been shown to have a significant effect on impulse buying. These findings reflect that impulsive shopping behavior among Shopee students in Banyuwangi is more influenced by hedonistic aspects of promotion and motivation than discounts or cashback alone, while still considering Islamic values in the decision-making process.